Analisis Profitabilitas Perusahaan Energi dengan Struktur Modal Sebagai Variabel Moderasi - Bayu, Bayu; Waharini, Faqiatul Mariya (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This research aims to determine the effect of company size, liquidity and managerial ownership on profitability with capital structure as a moderating variable (Study of Energy Sub-sector Companies Listed on the IDX for the period (2021 - 2023). This research uses a quantitative type of research using multiple regression analysis. The sampling technique uses purposive sampling, and a sample of 22 energy sub-sector companies for the 2021-2023 period is obtained. The research results show that the company size variable has a negative but not significant influence on profitability, Liquidity has a positive but not significant influence on profitability, managerial ownership has a positive but not significant influence on profitability. In the results of the Moderate Regression Analysis (MRA) test, the capital structure variable is not able to act as a moderator in the relationship between liquidity and profitability, capital structure is not able to act as a moderator in the relationship between managerial ownership and profitability, and the variable AR(1) has a positive but not significant effect on profitability.